Speculative & science fiction - Nwankwo, Chimalum Moses, 1949-; Egbunike, Louisa Uchum (African literature today, 2021)
"Over the past two decades, there has been a resurgence in the writing of African and African diaspora speculative and science fiction writing. Discussions around the 'rise' of science-fiction and fantasy have led to a push-back by writers and scholars who have suggested that this is not a new phenomenon in African literature. This collection focuses on the need to recalibrate ways of reading and categorising this grenre of African writing through critical examinations both of classics such as Kojo Laing's Woman of the Aeroplanes (1988) and Ngũgĩ wa Thiong'o's oeuvre, as well as more recent fiction from writers including Nnedi Okorafor, Namwali Serpell and Masande Ntshanga."--Back cover.